Efeito do treinamento físico combinado sobre os indicadores de estresse oxidativo e inflamação na musculatura esquelética periférica e respiratória em modelo experimental de hipertensão arterial pulmonar - Freire, Thais de Carvalho (2023)
The Pulmonary arterial hypertension (PAH) is a progressive disease with an unfavorable prognosis, characterized by pulmonary vasoconstriction and progressive pulmonary vascular remodeling. In PAH, combined physical training (CT) (i.e., the combination of aerobic and resistance training) is recommended as an adjuvant tool in the treatment of stable patients. The objectives of this dissertation were to review the respiratory and cardiovascular mechanisms involved in the pathophysiology of PAH (Study I) and to evaluate the effect of combined CT on oxidative stress (OS) variables and inflammatory mediators in peripheral and respiratory skeletal muscles in an experimental model of PAH (Study II). In Study I, a systematic review of pre-clinical and clinical studies in the last 10 years was conducted, supporting the integrated nature of PAH pathophysiology through functional and structural changes in peripheral reflexes, respiratory, cardiovascular, and musculoskeletal systems. Findings suggest future therapeutic targets that may improve exercise tolerance and quality of life in PAH patients. In Study II, we conducted an original protocol where Wistar rats received subcutaneous injection of MCT (40 µg/kg body weight) or saline and were divided into groups after 4 weeks: CT groups (MCTCT and SALCT - aerobic: 40-60% MaxSpeed, 3x/week; resistance: 40-60% MaxLoad, 2x/week) and sedentary groups (MCTSED and SALSED). Gastrocnemius and diaphragm muscles were assessed for oxidative damage markers (lipid peroxidation and carbonylated proteins), antioxidants (catalase, superoxide dismutase, FRAP), and pro-oxidants (hydrogen peroxide, NADPH oxidase), as well as inflammatory markers (interleukins IL-6 and IL-10 and TNF-α). PAH resulted in reduced antioxidant defense in the gastrocnemius and increased pro-oxidants and oxidative damage in both muscles. There was a reduction in the pro-inflammatory mediator (TNF-α) in the gastrocnemius and an increase in pro-inflammatory mediators and a decrease in anti-inflammatory mediators in the diaphragm. CT, on the other hand, partially normalized the redox balance in peripheral and respiratory muscles and the inflammatory mediators in respiratory muscles in PAH. In conclusion, the results reinforce the current understanding that PAH pathophysiology involves not only the cardiovascular and pulmonary systems but also the musculoskeletal system. Furthermore, original data presented in Study II support the understanding that changes in the inflammatory profile and redox balance occur in stable PAH and indicate moderate-intensity combined CT as an effective therapeutic strategy to prevent such alterations.